INFLUENCE OF ICT ON TWENTY-FIRST CENTURY PUBLISHING - AFULIKE, Don Christian; IHECHU, Innocent Paschal; UCHECHUKWU, Ify Lilian; ANUMADU, Adaeze Victory; OGWO, Okechukwu Kalu (Socialscientia: Journal of Social Sciences and Humanities, 2019)
The study examines the extent information and communication technology (ICT) has affected 21st century publishing. With the advances in ICT, electronic books and publishing, electronic journals, and the internet, which have launched the world into an information age; facilitation of quick and easy information and information resources for publishing is assured. This study adopted qualitative methods of participant observation (for select printing and publishing houses) and focus group discussions (with students of select tertiary institutions) to explore the implications of, access to, use and operations of information and communication technology. It was discovered that exposure to every bit of a published material on the platforms of information and communication technology (ICT) could in one way or the other influence hearts and mind or even shape opinion in this 21st Century age of globalization, while the application of ICT reduces man power and equally saves time. The study recommends the adoption of ICT in every aspect of the publishing environment as well as training and retraining of publishing personnel.